2017
DOI: 10.18632/oncotarget.22855
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin up-regulates the expression of the GATA-4 transcription factor and increases testosterone secretion from Leydig cells through RORα signaling in anin vitrogoat spermatogonial stem cell differentiation culture system

Abstract: Because androgen function is regulated by its receptors, androgen-androgen receptor signaling is crucial for regulating spermatogenesis. Androgen is mainly testosterone secreted by testis. Based on the results of early studies in goats, the administration of melatonin over an extended period of time increases steroid production, but the underlying mechanism remains unclear. Here, we report the expression of the melatonin membrane receptors MT1 and MT2 and the retinoic acid receptor-related orphan receptor-alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 88 publications
(77 reference statements)
3
22
0
Order By: Relevance
“…The analysis results indicate that the 16 bp indel was very strongly associated with goat first-born litter size. Compared with direct analysis in the tested population (Deng et al, 2017a ), this new strategy may provide more detailed and reliable results of association analysis. Additionally, the 16 bp locus had a significant effect on KDM6A gene expression, further implying a huge potential application for analysis of this locus.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis results indicate that the 16 bp indel was very strongly associated with goat first-born litter size. Compared with direct analysis in the tested population (Deng et al, 2017a ), this new strategy may provide more detailed and reliable results of association analysis. Additionally, the 16 bp locus had a significant effect on KDM6A gene expression, further implying a huge potential application for analysis of this locus.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of RORα nuclear receptors were reported in various tissues including testis, where a relationship between Sertoli cells functions and RORα was detected [ 36 ]. Furthermore, RORα expression and melatonin membrane receptors were recently detected in sheep [ 37 ] and goat [ 38 ] Leydig cells. In the present study, Retinoid-related orphan receptor (RORα)-deficient mice showed age-related progressive damage in the testis tubules and interstitium as well as a massive degeneration in spermatids that lead to decrease in the number of sperms.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin increases GATA-4 expression to induce testosterone synthesis by Leydig cells, promoting consequently more active meiosis and spermatid differentiation [ 38 ]. In this regard, the present study revealed an increase in the cellular activity of Leydig cells in the melatonin group, associated with an increase in the number of mitochondria and secretory granules.…”
Section: Discussionmentioning
confidence: 99%
“…CREB is an important transcription factor that is differentially regulated in various cell types. The cAMP responsive element modulator (CREM) is an important transcriptional activator during spermatogenesis, especially in postmeiotic germ cells [47]. Inactivation of CREM in mice resulted in an increased rate of apoptosis in the round spermatozoon stage, and the simultaneous expression of apoptosis-related genes [48].…”
Section: Discussionmentioning
confidence: 99%